Basic Research Interleukin-6 and the IL-6 (–174) C/G polymorphism in breast pathologies and in HIV-infected patients - Jabłonowska, Elżbieta; Kołacinska, Agnieszka; Kuydowicz, Jan; Przybyłowska, Karolina; Jabłonowski, Zbigniew (Archives of Medical Science, 2010)
Introduction : Breast cancer and acquired immunodeficiency syndrome (AIDS) are key issues for modern medicine. The aim of the current study was to present how cytokines, in the example of IL-6 and its polymorphism, can affect these two conditions. Material and methods : Thirty-one women with benign breast tumours, 42 breast cancer patients and 40 HIV-infected females were enrolled in the study. Serum IL-6 levels were determined by ELISA. The IL-6 polymorphism was genotyped by PCR-RFLP. Results : Serum IL-6 in patients with benign breast tumours was significantly lower than in females with breast cancer (p = 0.017) and HIV-infected women (p = 0.032). We did not find statistically significant differences in serum IL-6 level between females with breast cancer and HIV-infected women (p = 0.749). Comparing the distribution of genotypes and frequency of the IL-6 (–174) C/G polymorphism between the three study groups – breast cancer patients, patients with benign breast tumours, and HIV-infected patients – we did not find any statistically significant differences. Conclusions : IL-6 can play an important role in pathogenesis of breast cancer and HIV infection and its level is higher than in the control group irrespective of distribution of genotypes and frequency of the IL-6 (–174) C/G polymorphism.